Recruitment patterns of the scapular rotator muscles in freestyle swimmers with subacromial impingement - Wadsworth, D. J.; Bullock-Saxton, J. E. (International Journal of Sports Medicine, 1997)
Athletes with shoulder pathology consistently demonstrate abnormalities in scapular rotator activity, suggesting that muscle dysfunction is a factor to consider in the aetiology or recurrence of shoulder pain. However, one important measure of the coordinated activity between the scapular rotators, their timing or temporal recruitment pattern, remains undetermined. The purposes of this study were to 1. provide normative data on the temporal recruitment pattern of the scapular rotators in freestyle swimmers, 2. determine the effect of a unilateral shoulder injury on this pattern, 3. determine whether these effects extend to the non-injured side, and 4. determine the effect of injury on the consistency (variability) of muscle recruitment. Surface EMG data for the upper and lower trapezius and serratus anterior were recorded bilaterally from two groups of competitive freestyle swimmers during controlled bilateralelevation in the plane of the scapula. An injured group comprising nine swimmers with unilateral shoulder pathology and a control group of nine non-injured swimmers were included. Temporal data determined for the onset of muscle activation for each muscle were then compared between groups using an ANOVA and a one-sided F test. The results of the study indicate that in non-injured swimmers, upper trapezius is activated 217 ms prior to shoulder motion, followed by serratus anterior activation 53 ms after motion commences. Lower trapezius was not recruited until 349 ms after shoulder motion, when the arm had attained 15 degrees elevation. In injured swimmers, all three muscles on the injured side displayed significantly increased variability in the timing of activation (p < 0.05), whilst the serratus anterior was significantly delayed in its activation on the non-injured side (p < 0.05). Skill hand preference was shown to have no effect on muscle recruitment. The findings of this study indicate that a relationship does exist between shoulder injury and the temporal recruitment patterns of the scapular rotators, such that injury reduces the consistency of muscle recruitment. They further suggest that injured subjects have muscle function deficits on their unaffected side.